2016
DOI: 10.3310/hta20850
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of Donor Ex Vivo Lung Perfusion in UK lung transplantation: DEVELOP-UK

Abstract: BackgroundMany patients awaiting lung transplantation die before a donor organ becomes available. Ex vivo lung perfusion (EVLP) allows initially unusable donor lungs to be assessed and reconditioned for clinical use.ObjectiveThe objective of the Donor Ex Vivo Lung Perfusion in UK lung transplantation study was to evaluate the clinical effectiveness and cost-effectiveness of EVLP in increasing UK lung transplant activity.DesignA multicentre, unblinded, non-randomised, non-inferiority observational study to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 76 publications
2
115
0
1
Order By: Relevance
“…51,52 A large multicenter trial in the UK, however, found higher rates of grade 3 PGD, need for post-transplant ECMO, significantly increased cost, and almost double the one year mortality for patients who received EVLP lungs. 53 Although the authors caution drawing conclusions given the small number of patients involved (18 in the EVLP arm) and a change in the EVLP protocol midway through the trial, these findings suggest that further standardization of EVLP techniques may be necessary to allow effective, wide-spread adoption of this technology.…”
Section: Donor Managementmentioning
confidence: 99%
“…51,52 A large multicenter trial in the UK, however, found higher rates of grade 3 PGD, need for post-transplant ECMO, significantly increased cost, and almost double the one year mortality for patients who received EVLP lungs. 53 Although the authors caution drawing conclusions given the small number of patients involved (18 in the EVLP arm) and a change in the EVLP protocol midway through the trial, these findings suggest that further standardization of EVLP techniques may be necessary to allow effective, wide-spread adoption of this technology.…”
Section: Donor Managementmentioning
confidence: 99%
“…Several large clinical trials confirmed that this allows for a significant expansion of the donor lungs available for transplantation. For example, in a British multicenter study involving selected lungs that were deemed unsuitable for transplantation by conventional standards, it was possible to use one‐third of these organs for transplantation after evaluation with EVLP . Ongoing research in this area focuses on identifying further measurable parameters during EVLP that may serve to predict successful transplantation …”
Section: Indications For Evlpmentioning
confidence: 99%
“…Finally, several groups have used lungs from DCDs after ex vivo assessment with outcomes comparable to using without ex vivo and some of these proclaimed using ex vivo will improve DCD lung selection, and increased the uses of DCD lungs (9,16,(43)(44)(45). The conversion rate from EVLP to transplantation varies between 46 and 87% (15,(30)(31)(32)(37)(38)(39)(40)(41)(42)(43).…”
Section: Assessment During Evlpmentioning
confidence: 99%